Luther und die Reformation: Erwägungen und Kritik im Spiegel aktueller Literatur - Retter, Hein (International Dialogues on Education Journal, 2017)
The literary production on Luther has been in full swing for more than a year – with impressive results. This contribution is looking at the current view of Martin Luther by historians, church historians and literary authors. The following themes are dealt with through examples from the literature: Luther’s roots in the Middle Ages – Outstanding achievements – Treasures of the Reformation in words and images – The special approach to Luther – Critique of Luther from a post-Christian perspective – Luther and the Catholics – The future of churches.